The Great Disruptor
XI, 221 p. 10 illus., 9 illus. in color.
Keywords: The book examines Donald Trump’s populist politics of emotion from a culture and media studies perspective, highlighting the communicative strategies of provocation used by the President of the United States to generate approval and support of society. It also explores the role of both traditional and new media. The contributions in this volume place the “Great Disruptor” within a tension-filled field of popular culture, polarized public discourse, and rhetorical hostility. Lars Koch is a professor of modern German literature and media culture at the Technical University of Dresden, Germany. Tobias Nanz is a research associate at the professorship for European media studies at the Europa-Universität Flensburg, Germany and, as part of his Marie Skłodowska-Curie Fellowship, an associate professor at the Department of Culture and Language at the University of Southern Denmark. Christina Rogers is coordinator of gender and diversity projects for the first Executive Vice President of the Freie Universität Berlin, Germany.